Crystal structure of trans-(1, 8-dibutyl-1, 3, 6, 8, 10, 13-hexaazacyclotetradecane-κ4N3, N6, N10, N13)bis(isonicotinato-κO)copper(II) from synchrotron data. (February 2015) - Shin, J. W.; Kim, D.-W.; Kim, J. H.; Moon, D.
No abstract available